2006
DOI: 10.1105/tpc.105.040097
|View full text |Cite
|
Sign up to set email alerts
|

CONSTITUTIVELY PHOTOMORPHOGENIC1 Is Required for the UV-B Response in Arabidopsis

Abstract: CONSTITUTIVELY PHOTOMORPHOGENIC1 (COP1) is a negative regulator of photomorphogenesis in Arabidopsis thaliana. COP1 functions as an E3 ubiquitin ligase, targeting select proteins for proteasomal degradation in plants as well as in mammals. Among its substrates is the basic domain/leucine zipper (bZIP) transcription factor ELONGATED HYPOCOTYL5 (HY5), one of the key regulators of photomorphogenesis under all light qualities, including UV-B responses required for tolerance to this environmental threat. Here, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
481
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(504 citation statements)
references
References 58 publications
20
481
1
2
Order By: Relevance
“…Among the R2R3 MYB, it has been demonstrated that the maize P gene (ZmP) and its Arabidopsis functional homolog MYB12 control the transcriptional activation of the phenylpropanoid biosynthetic genes chalcone synthase (CHS), chalcone isomerase (CHI), flavonone 3-hydroxylase (F3H) and flavonol synthase 1 (FLS1) (Grotewold 2005;Mehrtens et al 2005;Luo et al 2008). Furthermore, it was reported that ZmP as well as MYB12 are up-regulated by UV-B exposure (Casati & Walbot 2005;Oravecz et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among the R2R3 MYB, it has been demonstrated that the maize P gene (ZmP) and its Arabidopsis functional homolog MYB12 control the transcriptional activation of the phenylpropanoid biosynthetic genes chalcone synthase (CHS), chalcone isomerase (CHI), flavonone 3-hydroxylase (F3H) and flavonol synthase 1 (FLS1) (Grotewold 2005;Mehrtens et al 2005;Luo et al 2008). Furthermore, it was reported that ZmP as well as MYB12 are up-regulated by UV-B exposure (Casati & Walbot 2005;Oravecz et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Suesslin and Frohnmeyer (8) discovered a putative UV-B photoreceptor or, at least, an important component of the UV-B transduction signaling. This finding contributes, together with other important data (9)(10)(11), to better clarify the postulated existence of a stress-independent UV-B signaling pathway in plants. On the contrary, it is established that plant phytochromes and cryptochromes are not the UV-B photoreceptors, even if UV-A may play a role in UV-B signal transduction (12).…”
Section: Introductionmentioning
confidence: 99%
“…The function of COP1 as an E3 ubiquitin ligase is impeded by light, resulting in activation of positive transcription factors to promote light response [10]. However, COP1 is a critical positive regulator of UV-B responses, contrasting to its function in light signaling [12]. HY5 is another important component shared by light and UV-B signaling.…”
Section: Introductionmentioning
confidence: 99%
“…HY5 is another important component shared by light and UV-B signaling. It is a bZIP transcription factor that positively regulates light-responsive gene expression [11], and it is required for plant survival under UV-B radiation [12]. COP1 is required for UV-B-induced HY5 gene activation, and both COP1 and HY5 proteins accumulate in the nucleus under UV-B [12], suggesting that HY5 is not the target of COP1 for degradation in UV-B signaling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation